Gas phase glycerol dehydration to acrolein over supported silicotungstic acid catalyst - Amin Talebian Kiakalaieh, 1984- author; Nor Aishah Saidina Amin, 1963- supervisor; Fakulti Kejuruteraan Kimia (2015)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2015